Dental management of a patient with 22q11.2 deletion syndrome (22q11.2DS). (18th September 2018) - AlQarni, Mohammed Ali; Alharbi, Adel; Merdad, Leena
Abstract : 22q11.2 deletion syndrome (22q11.2DS) is one of the most common microdeletion syndromes, with an incidence of approximately 1/2000–1/4000 live births; it is thought to be mainly attributable to a de novo deletion. The clinical phenotype of this syndrome is highly variable. Certain craniofacial and oral features are common to most patients with 22q11.2DS, including a high prevalence of dental caries; abnormalities of tooth shape, eruption and number; and enamel defects such as hypomineralisation and hypoplasia. This report focuses on the dental features and management of an 8-year-old boy with 22q11.2DS. Dental treatments were carried out under general anaesthesia. In summary, facial dysmorphism and common dental manifestations are typically noticeable in patients with this syndrome. Therefore, dentists need to be aware of the dental features of this condition in order to refer them to the adequate specialists. Cooperation among and experience with different specialties are mandatory to improve quality of life for patients with 22q11.2DS.